The Chicago Obsession in the Interpretation of US Antitrust History - Kovacic, William E. (The University of Chicago law review, 2020)
Discussions about the evolution of the US antitrust system since the early 1970s often dwell upon the influence of the Chicago School in shaping substantive rules and enforcement policy. Many commentators attribute to Chicago School scholars-most notably, Judge Robert Bork-the decisive role in gaining broad acceptance for permissive standards governing mergers, vertical restraints, and dominant firm behavior. In numerous treatments, the Chicago School is seen to be the intellectual foundation for US antitrust policy, including its acceptance of a "consumer welfare" standard that is said to focus exclusively on efficiency considerations to the exclusion of other policy objectives.